Formulation and Characterization of Cefixime Phytosomes for Oral Drug Delivery - Jain, Saloni; Ancheriya, Rahul; Srivastva, S; Soni, Shankar lal; Sharma, Mukesh (Asian Journal of Pharmaceutical Research and Development, 2019)
Novel drug delivery systems (NDDS) are one of the most strategies which enable to overcome the problems related to drug bioavailability. It is the rate and extent to which a drug becomes available to the target tissue after its administration. Over the last century, phyto-chemical science and phyto-pharmacological science established numerous plant compounds with various biological activities and health promoting benefits such as anti-mutagenicity, anti-carcinogenicity and anti-oxidative activity, for age-related diseases namely memory loss, osteoporosis, diabetic wounds, immune and liver disorders, etc. Herbal medicines have been known since eons for their safety, efficacy, folk acceptability and fewer side effects.